Conocimientos y actitudes preventivas sobre el virus del papiloma humano en estudiantes de Derecho de la Universidad Nacional de Loja - Pineda Armijos, Vilma Soraya (2016)
More than 100 years it has been considered that cervical cancer has an infectious cause associated with the human papillomavirus (HPV) virus, virology and clinical manifestations of this virus are the essential link in the development of neoplastic process (Consuegra, Molina, Egea, Garavito, 2009). The OMS said that in 2014 the cervical cancer, was the second type of most common cancer in women in less-developed regions. Epidemiological studies of injuries cervical premalignant have shown a strong association between sexual practice and the appearance of malignant tumors, women with multiple sexual patterns, pregnancies and interruptions at early age and stories of infections, increase the risk of developing the disease. Present research of descriptive and transversal type with quantitative approach, aimed at general characterize knowledge and preventive attitudes of the students of the career of law of the National University of Loja, 208 women participated in the study, information was collected through a survey. The results correspond to that more than half of the participants have knowledge disease, transmission mode, recognizes which are the signs and symptoms, while 46.2% does not know about the relationship of virus human papilloma and cancer cervical; the preventive attitudes that the students carry out examination of the PAP is, protection with condom or condom, however the 75.1% did not receive three doses of the vaccine for the human papilloma virus. KEY WORD: Human papillomavirus, knowledge, attitudes.